The Validity of the Discovery Learning Model to Improve Students Creative Thinking Skills - Kari, Dwi Septia; Ayub, Syahrial; Verawati, Ni Nyoman Sri Putu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to determine the validity of the product in the form of learning tools based on discovery learning models to improve creative thingking skills of students on momentum and impulse material. The type of research that used in this research is R&D (Research and Development) with a 4D model namely define, design, develop and disseminate. The products develop are syllabus, Learning implementation plan, teaching materials, Student worksheet and creative thingking ability test instruments. Validity data was obtained from the results of filling out the validation sheet by six validators, namely three expert validators and three practitioner validators. The validation sheets is filling by likert scale of 1-4. The percentage of validity results by expert validators has an average value of 84.82% with a fairly valid category. And the results of the validity value by the practitioner validators have an average value of 94.12% with a very valid category. The result of this study indicate that learning devices based on discovery learning models to improve students creative thinking skills are valid for use in learning at school.